Lexical and semantic features of translating names of Kazakh national clothing (Eurasian Journal of Philology Science and Education, 2023)
The article provides information about the fact that in the distant Paleolithic – Stone Age, humanity began to create leather and textile clothing using bone needles, bones, and other types of clothing culture, along with the use of clothing without seams.In the Neolithic period, the profession of weaving, spinning and weaving developed, and when we consider the types of clothing worn on the shoulders and waist from a linguistic point of view, they have their own names, depending on their specific functions and national characteristics.The appearance of names related to clothing has enriched the vocabulary of our language. The peculiarities of translating the names of national clothes into other languages, including English, belonging to the West German group, can be considered as the relevance of scientific work because such complex scientific research is proposed for the first time.The practical significance of scientific work is to use the results of research work in the field of literature, translation, reading and understanding of texts, compiling dictionaries, preparing scientific reports, training in educational programs in the textile industry and design.The comparative method and the method of translation analysis were used in the scientific work. Keywords: linguistics, translation, transcription, transliteration, calculus, close translation, clothing names, lexical and semantic specifics